Tanggung Jawab Hukum Marketplace Terhadap Konsumen Dalam Kasus Wanprestasi Transaksi Online - Delon Austin Sirait; July Esther (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
The development of digital technology has driven the growth of buying and selling transactions through marketplace platforms. However, this phenomenon is not free from the risk of default by sellers, such as delivery of goods that do not match, late delivery, or goods not delivered at all. In this context, marketplaces as digital platform providers have a strategic role in providing legal protection for consumers. This study aims to examine the definition of default in online transactions according to Indonesian law, analyze the forms of marketplace legal responsibility, identify legal remedies that consumers can take, and evaluate consumer legal protection based on applicable laws and regulations. The research method used is a literature study with a qualitative approach. The results show that default in online transactions constitutes a violation of electronic contracts as regulated in the Civil Code and the ITE Law. Marketplaces can be held legally responsible if they are negligent in carrying out their obligations to supervise and protect consumers. Consumers have the right to pursue legal remedies through complaints to the National Consumer Protection Agency (BPKN), the Non-Governmental Consumer Protection Agency (LPKSM), or through litigation. Regulations that protect consumers include Law No. 8 of 1999 concerning Consumer Protection and the ITE Law. This research contributes to strengthening the legal position of consumers in the digital commerce ecosystem.